Gene expression analysis in Cutaneous T-Cell Lymphomas (CTCL) highlights disease heterogeneity and potential diagnostic and prognostic indicators. (4th May 2017) - Litvinov, Ivan V.; Tetzlaff, Michael T.; Thibault, Philippe; Gangar, Pamela; Moreau, Linda; Watters, Andrew K.; Netchiporouk, Elena; Pehr, Kevin; Prieto, Victor G.; Rahme, Elham; Provost, Nathalie; Gilbert, Martin; et al.
ABSTRACT: Cutaneous T-Cell Lymphomas (CTCL) are rare, but potentially devastating malignancies, whose pathogenesis remains poorly elucidated. Unfortunately, currently it is not possible to predict based on the available criteria in which patients the cancer will progress and which patients will experience an indolent disease course. Furthermore, at early stages this malignancy often masquerades as psoriasis, chronic eczema or other benign inflammatory dermatoses. As a result, it takes on average 6 y to diagnose this lymphoma since its initial presentation. In this study, we performed transcription expression profiling using TruSeq targeted RNA gene expression on 181 fresh and formalin-fixed and paraffin-embedded (FFPE) skin samples from CTCL patients and patients affected by benign inflammatory dermatoses that often mimic CTCL clinically and on histology (e.g., psoriasis, chronic eczema, etc.) We also analyzed multiple longitudinal biopsies that were obtained from the same patients over time. Our results underscore significant molecular heterogeneity with respect to gene expression between different patients and even within the same patients over time. Our study also confirmed TOX, FYB, LEF1, CCR4, ITK, EED, POU2AF, IL26, STAT5, BLK, GTSF1 and PSORS1C2 genes as being differentially expressed between CTCL and benign skin biopsies. In addition, we found that differential expression for a subset of these markers (e.g., TOX, FYB, GTSF1 and CCR4 ) may be useful in prognosticating this disease. This research, combined with other molecular analyses, prepares the foundation for the development of personalized molecular approach toward diagnosis and management of CTCL.